Optimization of Human Rights Against Children in Domestic Violence Based on Law Number 35 of 2014 concerning Child Protection in Bandung City - Fadhil Musyaffa; Lola Vianda; Iqbal Fathur Rizqi (Jurnal Restorasi : Hukum dan Politik, 2024)
Within households (KDRT) in Bandung City. The family, as the smallest unit in society, should be a place of protection and love. However, reality shows that conflict in the household can lead to violence, with economic factors and childhood upbringing as triggers, as stated by the SAPA Foundation. The negative stigma in society towards domestic violence causes many victims to be reluctant to report the incident. Legal protection and human rights (HAM) for child victims of domestic violence are regulated in Law Number 35 of 2014 concerning Child Protection. However, there needs to be better implementation so that children's rights are truly protected. Preventing and anticipating negative impacts on child victims is an important step, by paying attention to the principles of protection, providing support for facilities and infrastructure, as well as cross-sector coordination. The SAPA Foundation has been active in efforts to prevent domestic violence against children, including through community-based services (LBK) and counseling. However, there are still big challenges, especially in overcoming family economic problems and psychological stress that trigger violence. In order to create a safe and supportive environment for children to engage, the active participation of communities and stakeholders is key. Public awareness about the importance of preventing domestic violence needs to be increased, and collaborative efforts between institutions, government, and society are crucial in overcoming this complex problem.